Effect Of Aggregate to Cement Ratio On The Performance of Pervious Concrete - Kiew, Jie Fu (2018)
Pervious concrete is a special concrete mixture designed to allow water infiltration. The effect of aggregate to cement ratio on the performance of pervious concrete is evaluated. The optimized aggregate to cement ratio used in pervious cement had been indicated. Several task such as compressive strength test, density test, porosity test and constant head water permeability test were conducted to determine the optimum aggregate to cement ratio incorporating 3:1, 4:1, 5:2 and 6:1. Specimen with higher aggregate to cement ratio achieve higher compressive strength and density but lower porosity and permeability. The result shown that specimen with 3:1 aggregate to cement ratio achieved highest average density of 1974 kg/m3 and lowest porosity of 26.3 percent. Besides, specimen with 3:1 aggregate to cement ratio also achieve highest average compressive strength of 12.14 MPa and acceptable water permeability and porosity to cement at 28th day. On the other hand, the result indicate the specimen with 6:1 aggregate to cement ratio achieved lowest average compressive strength of 5.04 MPa and highest water permeability of 2.93 cm/s. Flaky shape of coarse aggregate which limited the compressive strength of pervious specimen achieved is not recommended to use.